On some recent taxonomic advancement and the resultant problems in the arboreal skink genus Dasia Gray, 1839 (Reptilia: Scincidae) - Chandramouli, S. R.; Amarasinghe, A. A. Thasun (Zootaxa, 2015)
South Asian members of the arboreal skink genus Dasia Gray, 1839 were recently reviewed using morphological and molecular approaches (Wickramasinghe et al. 2011; Harikrishnan et al. 2012). Harikrishnan et al. (2012) described a new species, Dasia johnsinghi, from South India. Both reviews add considerably to our taxonomic knowledge of the genus, but are unfortunately marred by several inaccuracies and lapses in taxonomic and nomenclatural practice. Taxonomic research is socially relevant because it contributes to the understanding of biodiversity (Bhat & Sarma, 2014) and it is responsible for laying the foundation for conservation (Dubois 2003; Evenhaus 2007); consequently, we believe taxonomists must take responsibility for maintaining publication quality, to promote conservation and science, and in this case, herpetology. While pernicious descriptions are harmful to the growth of herpetology in the region [i.e. the Western Ghats] (Vasudevan et al. 2007) in a time expecting quality science (Shanker, 2014) inaccuracies and errors in taxonomic literature should be carefully guarded against.